DNA‐binding domain as the minimal region driving RNA‐dependent liquid–liquid phase separation of androgen receptor. (7th May 2021) - Ahmed, Junaid; Meszaros, Attila; Lazar, Tamas; Tompa, Peter
Abstract: Androgen receptor (AR) is a nuclear hormone receptor that regulates the transcription of genes involved in the development of testis, prostate and the nervous system. Misregulation of AR is a major driver of prostate cancer (PC). The primary agonist of full‐length AR is testosterone, whereas its splice variants, for example, AR‐v7 implicated in cancer may lack a ligand‐binding domain and are thus devoid of proper hormonal control. Recently, it was demonstrated that full‐length AR, but not AR‐v7, can undergo liquid–liquid phase separation (LLPS) in a cellular model of PC. In a detailed bioinformatics and deletion analysis, we have analyzed which AR region is responsible for LLPS. We found that its DNA‐binding domain (DBD) can bind RNA and can undergo RNA‐dependent LLPS. RNA regulates its LLPS in a reentrant manner, that is, it has an inhibitory effect at higher concentrations. As RNA binds DBD more weakly than DNA, while both RNA and DNA localizes into AR droplets, its LLPS depends on the relative concentration of the two nucleic acids. The region immediately preceding DBD has no effect on the LLPS propensity of AR, whereas the functional part of its long N‐terminal disordered transactivation domain termed activation function 1 (AF1) inhibits AR‐v7 phase separation. We suggest that the resulting diminished LLPS tendency of AR‐v7 may contribute to the misregulation of the transcription function of AR in prostate cancer.